Reduced audiovisual recalibration in the elderly - Chan, Yu Man; Pianta, Michael J.; McKendrick, Allison M. (Frontiers in Aging Neuroscience, 2014)
Perceived synchrony of visual and auditory signals can be altered by exposure to a stream of temporally offset stimulus pairs. Previous literature suggests that adapting to audiovisual temporal offsets is an important recalibration to correctly combine audiovisual stimuli into a single percept across a range of source distances. Healthy ageing results in synchrony perception over a wider range of temporally offset visual and auditory signals, independent of age-related unisensory declines in vision and hearing sensitivities. However the impact of ageing on audiovisual recalibration is unkonwn. Audiovisual synchrony perception for sound-lead and sound-lag stimuli was measured for fifteen younger (22-32 years old) and fifteen older (64-74 years old) healthy adults using a method-of-constant-stimuli, after adapting to a stream of visual and auditory pairs. The adaptation pairs were either synchronous or asynchronous (sound-lag of 230ms). The adaptation effect for each observer was computed as the shift in the mean of the individually fitted psychometric functions after adapting to asynchrony. Post adaptation to synchrony, the younger and older observers had average window widths (±standard deviation) of 326 (±80) and 448 (±105) ms, respectively. There was no adaptation effect for sound-lead pairs. Both the younger and older observers however perceived more sound-lag pairs as synchronous. The magnitude of the adaptation effect in the older observers was not correlated with how often they saw the adapting sound-lag stimuli as asynchronous nor their synchrony window widths. Our finding demonstrates that audiovisual synchrony perception adapts less with advancing age.